The Implementation of Value Co-Creation in the Food Industry - Yuliawati, Asri Anisa (International Research Journal of Business Studies, 2023)
In this study, we analyse, and classify the literature that discusses the implementation of value co-creation in the food industry. For this purpose, we conducted a systematic literature review identified from Scopus database search results. Then, it was further screened and filtered to obtain specific literature that could answer the proposed research question. Our analysis focuses on how those studies put value co-creation into real business and industrial contexts. We are looking at the value co-creation phases, mechanisms, and how those could create particular value. We found that value co-creation can be implemented in various ways tailored to the context that the actors wish to achieve. Another classification is made to find out the focus of the present research. This classification is based on the different functions they were focusing on across the food industry. Finally, we organise and summarise the suggestion for future research directions